Phenazine-1-carboxylic acid (PCA) from cold-adapted yeast Glaciozyma antarctica PI12 - Andi Rifki Rosandy; Rozida Mohd. Khalid (Current Research on Bioscences and Biotechnology, 2020)
A phenazine alkaloid, phenazine-1-carboxylic acid (PCA) was isolated from the ethyl acetate extract of cold-adapted yeast Glaciozyma antarctica PI12 (Kriegeriales). The compounds were isolated by several chromatography techniques i.e. radial chromatography (RC) and thin-layer chromatography (TLC). The chemical structure was elucidated by ultraviolet (UV), infrared (IR), nuclear magnetic resonance (1D and 2D NMR) spectroscopy and mass spectrometry.